Control de calidad de los radiofármacos - Noto, María Gracia; Mitta, Aldo Emilio Antonio (Federación Bioquímica de la Provincia de Buenos Aires; Argentina, 1979)
Fil: Noto, María Gracia Comisión Nacional de Energía Atómica; Argentina